Residential electric load curve profile based on fuzzy systems - Abreu, Thays [UNESP]; Alves, Uilian N.L.T [UNESP]; Minussi, Carlos R [UNESP]; Lotufo, Anna Diva P. [UNESP]; Lopes, Mara L. M. [UNESP] (Institute of Electrical and Electronics Engineers (IEEE), 2016)
Electric energy demand in residences represents around 30% of the global demand. This requires a detailed knowledge about the electrical load patterns, leading to a change in final consumer behavior to reduce the general demand. This work uses a fuzzy system, considering the quantity of occupants in a Brazilian family in different periods of day aiming to obtain the residential electric load profile.
Keywords: Active occupation; Fuzzy Logic; Residential Load Curve